Latinxs in La Migra: Why They Join and Why It Matters. (September 2021) - Cortez, David
Once an exclusively white enterprise, the last forty-five years have witnessed the emergence of a disproportionately Latinx immigration law enforcement workforce. This article addresses the question of why Latinxs elect to work for agencies that have systematically targeted the ethnic communities to which they belong. Where existing scholarship has often implied Latinxs may self-select into immigration law enforcement due to a lack of identification with the immigrant-experience, a dissociation with ethnic identity, and generally restrictionist immigration attitudes, this article finds little empirical evidence to support such an assumption. Analysis of interviews with sixty-one Latinx Immigration and Customs Enforcement (ICE) agents across Arizona, California, and Texas reveals, instead, Latinxs elect to work in immigration law enforcement in service of economic self-interest and survival, with "money, " "a good job, " and "benefits" cited as the primary motivation(s) behind applying for and accepting a job in immigration. This pattern holds irrespective of individual agents' levels of identification with the immigrant-experience and particular attitudes toward immigration, and suggests a diversity in the demographics of immigration law enforcement agencies that extends beyond mere race and ethnicity, to include a diversity of perspective and potential for empathy.